Drillstring Vibration Analysis in Extended Reach Drilling (ERD) using WELLPLANTM - MOHAMMED AHMED OMER, MOHAMMED AHMED (Universiti Teknologi Petronas, 2012)
Oil and gas industry always aims efficient service with optimal expenses. This final year project, aiming to deal with one of the most important parameters, that has tremendous impact on drilling operations’ time and cost. This parameter as mentioned above on the topic is a Drillstring Vibrations. While drilling, Drillstring Vibration causes premature drillstring components and bit failure [8], and is a waste of drilling energy. To increase drilling efficiency, drillstring vibrations need to be monitored and analyzed and the optimum drilling parameters and practices need to be achieved as a well is being drilled. This results in a reduction in the drillstring failures and the amount of time spent tripping and/or fishing, and an increase in both bit life and drilling rate. Drillstring dynamics is one of the most important limiting factors in extended reach drilling. This is because, long sections of the drillstring lie on the low side of the wellbore while rotating. When the rotary speed exceeds a critical threshold the drillstring starts to snake, sliding up and down the borehole wall [1]. If rotated further beyond the threshold speed, the drillstring will eventually start to whir which can cause severe damage to string components after only a short period of time [1]. Therefore, the main scope of the project, considering the earlier mentioned issues, a WELLPLAN software (Critical Speed Module) used. The project mainly dealt with drillstring, axial stress, bending stresses and torsional oscillations known as stick-slip motion of the bit. Besides the WELLPLANTM software, a matlab M.file was developed that uses some predetermined equations to estimate the critical drillstring vibrations, and critical operational speed taking into account the weight on bit, BHA length and rock compressive strength